The Effect of Sharia Share, Sukuk, Sharia Mutual Funds and Exchange on the National Economic Growth - Yani, Devi; Kismawadi, Early Ridho; Nasution, Ismail Fahmi Ar Rauf; Bahri, M. Irvanni (BISNIS, 2022)
The thesis entitled "The Influence of Sharia Sukuk Shares, Sharia Mutual Funds and Exchange Rates Against National Economic Growth" was written by Devi Yani aims to find out how much influence sharia stocks, Sukuk, Islamic mutual funds, and exchange rates have on the national economic growth in 2013-2018. quantitative with secondary data types and data used based on time series data. Data is obtained from the financial services authority (OJK) and Bank Indonesia. The variables used in this study are national economic growth as the dependent variable (Y), with the independent variables of sharia shares (X1), Sukuk (X2), Islamic mutual funds (X3), and exchange rates (X4). Data were analyzed using multiple linear regression analysis using the SPSS application. The results showed that partially sharia shares had a negative and significant effect with a significance value of 0.006 and t count of -3.088 for national economic growth. Sukuk had a positive and significant effect with a significance value of 0.001 t count of 4.191. positive sharia mutual funds and not significant with a significance value of 0.465 and t count of 0.648. in contrast, the negative effect rate is insignificant with a significance value of 0,000 and at a count of -6,506 for economic growth. Simultaneously it shows that Islamic stocks, Sukuk, Islamic mutual funds, and exchange rates on economic growth have a positive and significant influence on the dependent variable (economic growth) with a significance value of 0,000 and F count 11,542.